Modeling and analysis of dynamic systems - Esfandiari, Ramin S.; Lu, Bei (CRC Press, Taylor & Francis Group, 2018)
Written for senior level courses/modules, the textbook meticulously covers techniques for modeling a variety of engineering systems, methods of response analysis, and introductions to mechanical vibration, and to basic control systems. These features combine to provide students with a thorough knowledge of the mathematical modeling and analysis of dynamic systems.